Pengaruh e-WOM dan Brand Awareness Terhadap Keputusan Pembelian Jasa Kamar Secara Online di Grand Basko Hotel Padang - Elviona Rizky Ananda; Rian Surenda (Lembaga Pengembangan Kinerja Dosen, 2024)
This study was motivated by the discovery of a phenomenon found by researchers in purchasing decisions related to ewom and brand awareness in Grand Basko Hotel Padang. The research method used in this study is quantitative with a causal-associative approach (cause and effect) using the survey method. The population of this study included guests who have stayed at Grand Basko Hotel Padang. The research sample consisted of 110 respondents. The sampling method used was non-probability based sampling with the type of sampling i.e. purposive sampling. The instruments were tested with validity and reliability tests. The analysis requirements are tested with the normality test, heteroskedarity test and multicollinearity test. The hypothesis tests are performed with multiple linear regression tests, t-tests (partial), f-tests (simultaneous) and the coefficient of determination. The result of the R square is 0.849, which means that the ewom variable affects the purchase decision by 84.9%. The value for the R-square brand recognition can get 0.863 results. This means that the variables for brand recognition affect the purchase decision of Grand Basko Hotel Padang by 86.3%. The Adjusted R-squared (R²) value is 0.898, indicating that the combined influence of eWOM and brand awareness on purchase decisions is approximately 89.8%. The remaining 11.2% of the variation is influenced by other factors not discussed in this study.